Low pH gel intranasal sprays inactivate influenza viruses in vitro and protect ferrets against influenza infection - Lambkin-Williams Robert; Hull David; Charbonneau Duane; Bowtell Philip; Rennie Paul; Oxford John (Respiratory Research, 2007)
Abstract Background Developing strategies for controlling the severity of pandemic influenza is a global public health priority. In the event of a pandemic there may be a place for inexpensive, readily available, effective adjunctive therapies to support containment strategies such as prescription antivirals, vaccines, quarantine and restrictions on travel. Inactivation of virus in the intranasal environment is one possible approach. The work described here investigated the sensitivity of influenza viruses to low pH, and the activity of low pH nasal sprays on the course of an influenza infection in the ferret model. Methods Inactivation of influenza A and avian reassortment influenza was determined using in vitro solutions tests. Low pH nasal sprays were tested using the ferret model with an influenza A Sydney/5/97 challenge. Clinical measures were shed virus, weight loss and body temperature. Results The virus inactivation studies showed that influenza viruses are rapidly inactivated by contact with acid buffered solutions at pH 3.5. The titre of influenza A Sydney/5/97 [H3N2] was reduced by at least 3 log cycles with one minute contact with buffers based on simple acid mixtures such as L-pyroglutamic acid, succinic acid, citric acid and ascorbic acid. A pH 3.5 nasal gel composition containing pyroglutamic acid, succinic acid and zinc acetate reduced titres of influenza A Hong Kong/8/68 [H3N2] by 6 log cycles, and avian reassortment influenza A/Washington/897/80 X A Mallard/New York/6750/78 [H3N2] by 5 log cycles, with 1 min contact. Two ferret challenge studies, with influenza A Sydney/5/97, demonstrated a reduction in the severity of the disease with early application of low pH nasal sprays versus a saline control. In the first study there was decreased weight loss in the treatment groups. In the second study there were reductions in virus shedding and weight loss, most notably when a gelling agent was added to the low pH formulation. Conclusion These findings indicate the potential of a low pH nasal spray as an adjunct to current influenza therapies, and warrant further investigation in humans.